European economic forecast (Publications Office of the European Union, 2024)
This Winter interim Forecast lowers the growth outlook for this year and sets inflation on a lower downward path than projected last autumn. Economic activity in 2023 is now estimated to have expanded by only 0.5% in both the EU and the euro area. The growth outlook for 2024 is revised down to 0.9% in the EU and 0.8% in the euro area. In 2025, economic activity is still expected to expand by 1.7% in the EU and 1.5% in the euro area. EU HICP inflation is forecast to fall from 6.3% in 2023 to 3.0% in 2024 and 2.5% in 2025. In the euro area, it is projected to decelerate from 5.4% in 2023 to 2.7% in 2024 and to 2.2% in 2025.
10.2765/01964
Keywords: Graue Literatur; economic situation; economic policy; euro area; European Union; economic forecasting; economic growth; economic fluctuation; gross domestic product; climate change; Palestine question; EU Member State; report